Sistem Informasi Pelayanan Kesehatan Hewan Pada Klinik Dinas Peternakan Dan Kesehatan Hewan Kabupaten Sumbawa Berbasis Web - Syahidah, Khaula; Esabella, Shinta; Mardinata, Erwin (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
The development of a technology has the aim of increasing the productivity and effectiveness of users both from human resources and organizations / businesses. The Animal Clinic at the Sumbawa Livestock Service Office is an agency engaged in serving the community in caring for the health of livestock or pets. The development of the Sumbawa District Animal Husbandry and Animal Health Service clinic information system uses one of the methods that is part of the System Development Life Cycle (CDLC), namely Rapid Application Development (RAD) as a software development method that emphasizes development methods in a short and fast time cycle because the initial stage of development with the aim or discussion to determine user needs. Data collection is carried out by observing and analyzing the service process and making the manual recording process carried out into computerized so as to make it easier for the clinic to serve consumers and the community. The system design used is UML design which consists of use case diagrams, activity diagrams, sequence diagrams, and class diagrams. The system testing solution is using black box texting. and can be used as input for the Livestock and Animal Health Service Office of Sumbawa Regency for the management of data and information on animal health services.